The impact of artificial intelligence on China's labor market - ZHANG, YIFAN; Špecián, Petr; Lichard, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
The creation effect and substitution effect of artificial intelligence technology on labor force employment in China exist simultaneously, which will not only bring about changes in total employment but also cause changes in employment structure. In recent years, artificial intelligence technology in China has shown rapid development, which has triggered high attention from the society, and AI technology, as the core of the fourth technological revolution, will have a significant impact on human production, and lifestyle, in this context, this paper In this context, this paper investigates the impact of AI on the total amount and structure of employment in China through the ideas of theoretical analysis-empirical analysis-conclusions-suggestions. Firstly, this paper introduces the meaning and birth background of AI, then analyzes the substitution effect and creation effect brought by AI through the study of literature, followed by the calculation of AI index of each province in China using entropy value method, then collects and collates the employment volume of labor force, gross regional product, and average wage of labor force in 30 provinces and cities in China from 2010 to 2016, and by education level The labor force was classified into 3 indices: low, medium, and high skill labor force. Finally, a regression analysis model was constructed by empirical analysis and concluded that AI has a substitution effect on total labor force employment in China, but the substitution effect is significantly greater for low-skilled labor than for medium-skilled labor, while high-skilled labor will be affected by the creation effect and employment will increase. The paper concludes with suggestions on the current situation in China, hoping that the government, enterprises and workers will work together to face the challenges and opportunities brought by the development of AI technology.
Vedoucí práce: Petr Špecián
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses